Website use increases - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Almost 40% of Spore subscribers now have email, and some sort of access to the World Wide Web computer network. Two years ago, it was 12%.No wonder that the use of CTA's Website is growing. In early July 2002, it had 720 users a day, reading 2,000...